Pengaruh Variasi Waktu dan Kecepatan Pengadukan Terhadap Difusivitas dan Konstanta Reaksi Dengan Proses Ekstraksi Reaktif - Az Zahra , Clarisa Hany; Mustikaningrum , Mega; Sawali , Fikrah Dian Indrawati; Mustika, Pra Cipta Buana Wahyu (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
The world is experiencing a crisis of scarcity of diesel fuel sources. The B30 program is to develop energy sources by utilizing alternative energy sources to prevent petroleum shortages. This program also supports research, namely making biodiesel using non-edible raw materials. Apart from that, another benefit of this research is to determine the effect of time on the yield of biodiesel production, knowing the effect of stirring speed on the diffusivity constant and reaction speed constant of the reactive extraction process. Biodiesel production in this research uses a reactive extraction process. The raw materials used are mahogany seeds, the solvent is methanol, chloroform as a co-solvent, and KOH as a catalyst. This process uses a temperature of 65°C, reaction time of 40 and 80 minutes, and varying stirring speeds of 200 and 300 rpm. The effect of time with a variable stirring speed of 200 rpm the longer the resulting yield increases, while at a stirring speed of 300 rpm the resulting yield decreases. The yield obtained at 200 rpm stirring was 82.363% (40 minutes), 87.6366% (80 minutes), 84.7605% (40 minutes), and 78.7204 (80 minutes). For the methyl ester diffusion constant, the stirring speed of 200 rpm is 8,20 x 10-8 dm2/minute, while the stirring speed of 300 rpm is 8,17 x 10-8 dm2/minute. The reaction rate constant is 1.99 dm3/mol min.